PPAR γ Prevents Neuropathic Pain by Down-Regulating CX3CR1 and Attenuating M1 Activation of Microglia in the Spinal Cord of Rats Using a Sciatic Chronic Constriction Injury Model - Li, Xilei; Guo, Qulian; Ye, Zhi; Wang, E.; Zou, Wangyuan; Sun, Zhihua; He, Zhenghua; Zhong, Tao; Weng, Yingqi; Pan, Yundan (Frontiers in Neuroscience, 2021)
Background Previous studies have proved that peripheral nerve injury is involved in the pathogenesis of neuropathic pain (NP). The peripheral nerve injury primes spinal M1 microglia phenotype and produces pro-inflammatory cytokines, which are responsible for neurotoxic and neuronal hyper-excitable outcomes. Spinal peroxisome proliferator-activated receptor gamma (PPAR γ) has been shown to play an anti-inflammatory role in the development of NP. However, the role of PPAR γ in attenuating the pathological pathway of spinal microgliosis is still unknown. Methods Sprague-Dawley rats (male, aged 8–10 weeks) were randomly divided into three groups, i.e., a control group, a NP group, and a NP + lentivirus encoding PPAR γ (LV-PPAR γ) group. The sciatic chronic constriction injury (CCI) model was used to induce NP in rats. Pain behavior was assessed by monitoring the rat hind-paw withdrawal threshold to mechanical stimuli and withdrawal latency to radiant heat. The LV-PPAR γ was intrathecally infused 1 day before CCI. Western blot analysis and real-time qPCR were used to detect the microglia phenotypic molecules and CX3CR1 expression in the spinal cord. In vitro, BV-2 microglia cells were transfected with LV-PPAR γ and incubated with lipopolysaccharides (LPS), and the levels of M1 microglia phenotypic molecules and CX3CR1 in BV-2 microglia cells were assessed by western blot analysis, real-time qPCR, and enzyme-linked immunosorbent assay. Results Preoperative intrathecal infusion of LV-PPAR γ attenuated pain in rats 7 days post-CCI. The M1-microglia marker, CX3CR1, and pro-inflammatory signaling factors were increased in the spinal cord of CCI rats, while the preoperative intrathecal infusion of LV-PPAR γ attenuated these changes and increased the expression of IL-10. In vitro, the overexpression of PPAR γ in BV-2 cells reduced LPS-induced M1 microglia polarization and the levels of CX3CR1 and pro-inflammatory cytokines. Conclusion Intrathecal infusion of LV-PPAR γ exerts a protective effect on the development of NP induced by CCI in rats. The overexpression of PPAR γ may produce both analgesic and anti-inflammatory effects due to inhibition of the M1 phenotype and CX3CR1 signaling pathway in spinal microglia.